A Pragmatic Analysis of Clickbait Headlines in the Celebrity Rubric of Indozone - Salsabila, Regina; Djauhari, Otong Setiawan (Journal of Advance in Language, Literature, and Education, 2025)
This study examines implicature in celebrity clickbait headlines of the Indonesian online media platform Indozone. Framed by Grice’s Cooperative Principle (1975), which consists of the maxims of Quantity, Quality, Relevance, and Manner, the research identifies strategic violations of these maxims that generate reader inference. Using a qualitative-descriptive method, the study analyzes how such violations construct conversational implicatures that provoke curiosity and emotional engagement. The findings reveal that most headlines intentionally flout the maxims of Quantity, Manner, and Relevance by omitting key information, using vague or suggestive language, and emphasizing sensational or emotionally charged content. These pragmatic strategies manipulate attention and increase click-through rates. The study also highlights how implicature functions not only as a tool for communication but as a persuasive device in digital journalism. By situating the analysis within the Indonesian context, this research contributes to the field of pragmatics and media studies. It further calls for enhanced media literacy, suggesting that understanding implicature in headlines equips readers to interpret online content more critically and ethically.